2008
DOI: 10.1111/j.1442-2050.2000.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life study on four patients who underwent esophageal resection and delayed reconstruction for Boerhaave’s syndrome

Abstract: Boerhaave’s syndrome is the condition of spontaneous rupture of the esophagus as a consequence of the strain of emesis with or without predisposing esophageal disease. It is a condition with high mortality. We describe four patients who underwent a transthoracic esophagectomy to remove the rupture of the intrathoracic esophagus, closure of the esophageal gastric junction, fashioning of a feeding gastrostomy, and formation of a left cervical esophagostomy. Three patients underwent reconstruction with subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A thorough literature review revealed three previous publications that exclusively focused on HRQoL after benign esophageal perforations. Varghese et al published a case report of four cases with reduced HRQoL after esophageal resection due to Boerhaave syndrome (23).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…A thorough literature review revealed three previous publications that exclusively focused on HRQoL after benign esophageal perforations. Varghese et al published a case report of four cases with reduced HRQoL after esophageal resection due to Boerhaave syndrome (23).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%